(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
This article discusses the integration of information technology, the integration of assignments, the teaching of integration tasks on the basis of information technology, its effectiveness, methods and techniques, which serve to increase information competence in the process of working in mathematics lessons in primary school.